Towards a Poor Theatre - Grotowski, Jerzy 1933-1999; Barba, Eugenio; Brook, Peter (New York Routledge, 2002)
Originally published in 1968, Jerzy Grotowski's groundbreaking book is available once again. As a record of Grotowski's theatrical experiments, this book is an invaluable resource to students and theater practioners alike.
Keywords: Theater criticism